Child Development : An illustrated guide - Meggitt, Carolyn (Harlow, Essex : Pearson, 2012)
Fully updated and restructured so learners can match the new EYFS key areas and can be sure they have the most up-to-date information this book includes a DVD providing video clips of children's developmental stages at all ages which gives learners the opportunity to experience this important area of child development.
Previous edition: 2006.
Includes bibliographical references.
Keywords: Child development; Child Care